PREVALENCE OF DIGITAL CLUBBING IN HEALTH AND MALIGNANCY - BL, Preethi; T, Arulponni; K, Adarsh; J, Bhargav; N, Hanumanthappa; KP, Suresh (Pakistan Journal of Physiology, 2016)
Background: Digital clubbing is the oldest known clinical sign. Though asymptomatic, it often predicts the presence of some chronic underlying pulmonary, cardiovascular, neoplastic, hepatobiliary, mediastinal, endocrine, or gastrointestinal disease. Not much information is available on its association with malignancy. Clubbing has been commonly associated with lung cancer, more often in non-small cell lung carcinoma. The objective of this study was to evaluate the prevalence of digital clubbing in patients with Oral Cancer (solid tumours). Methods: In this case controlled study, cancer patients attending the Oncology outpatient and their age matched healthy subjects were included. The cancer patients were grouped as Cases and the Control groups. All subjects were evaluated clinically and a uniform protocol for clubbing evaluation was applied. Their habits and any underlying coexisting disease were noted. Results: Over a period of 6 months, 72 subjects were recruited for the study, of which 36 were patients with diagnosed malignancy (Cases) and 36 were normal healthy subjects (Controls). Male:Female ratio in Cases was 3:1 v/s 2.2:1 in Controls. Seventy-two percent of the Cases were tobacco smokers compared to 27.8% in controls. In Cancer patients digital clubbing was positive in 26 (72.2%) compared to 8 (22.2%) in healthy Controls (p<0.001). In Cases, 84.6% having clubbing were smokers compared to 70% in controls with clubbing. Conclusions: Digital clubbing is strongly associated with serious underlying disease like cancer and its implications are still a clinical enigma. A significant association of clubbing and tobacco smoking is observed in head and neck cancer patients. Pak J Physiol 2016;12(2):32–6